Fatores de estresse percebidos e comportamentos de enfrentamento de estudantes de enfermagem na prática clínica: um estudo transversal / The perceived stress factors and coping behaviors of nursing students in clinical practice: a cross-sectional study - inci mercan annak; Buse Nur Doganay; Cansu Dincel (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: the objective of this study was to determine the level of stress experienced by nursing students in clinical practice, the stressors that contribute to this stress, and the coping behaviors that nursing students employ to manage stress Method: the study employed a descriptive design. The data were collected via Google Forms between December 8, 2022, and June 2, 2023. Result: the mean age of the participants was 20.83±1.62 years and 28.1% were second-year nursing students. The most prevalent form of stress reported by the participants was the stress from taking care of patients, which was followed by the stress from teachers and nursing personnel and The most frequently reported coping strategies among the participants were avoidance. Conclusions: educators and nurses should recognize that errors are an inherent part of the learning process, understand the stress experienced by students, and provide support to enable them to focus on positive learning.